Red-mud additive geopolymer composites with eco-friendly aggregates - Uysal, Mucteba; Dilbas, Hasan; Cosgun, Turgay; Bendjilali, Fatiha (ELSEVIER SCI LTD, 2024)
Geopolymers have an increasing importance and a crucial task in engineering, especially structural engineering. Geopolymers are sustainable composites with low carbon emissions rather than cement composites. It leads to be an alternative to cement composites and the structure of geopolymer composites can allow to utilize various industrial and non-industrial wastes and by-products. In this point, there is an unclarity of waste material contributions to the geopolymeric composites and this issue is worth to study and an area of ongoing research. In this paper, it is aimed to produce red mud additive sustainable geopolymer composites with various eco-friendly fillers (brick powder, waste marble powder, glass powder, ceramic powder, and rice husk ash). 28 mixtures were designed, many specimens produced, and tested. In the first step of the experimental stage, the physical, the mechanical and the durability properties were determined and evaluated. At second, the best geopolymer composites were determined with a multi-criteria decision-making method (MCDM). 22 geopolymer parameters were employed in MCDM. As a results, 25% marble dust, 25% brick powder, 75% ceramic powder, 50% rice husk ash and 50% glass powder were the optimum ratios to obtain maximum compressive strength in terms of waste types and the highest compressive strength is obtained for 25% brick powder among the results. The best geopolymer composite was determined as GWGP50 with 50% glass powder + 50% recycled aggregate in a holistic manner with TOPSIS. Results showed that geopolymer GWGP50 had aspects that were open to development.
Keywords: Sustainability; Red mud; Geopolymer; Decision support method; Durability; SELF-COMPACTING CONCRETE; RICE HUSK ASH; MECHANICAL-PROPERTIES; CURING TEMPERATURE; WASTE; STRENGTH; MORTARS; SILICA; PERFORMANCE; Construction & Building Technology; Engineering; Materials Science